Assessment of the knowledge, attitudes, and practices toward human tuberculosis amongst rural communities in Chad - Didi, Lamireou; Abakar, Mahamat Fayiz; Bongo Naré Richard, Ngandolo; Djané, Adou; Kessely, Hamit; Issaka, Yaya; Diagbouba, Serge; Adrien Marie Gaston, Belem; Zinsstag, Jakob; Bonfoh, Bassirou; Dürr, Salome (Frontiers in Veterinary Science, 2024)
Tuberculosis (TB) is an infectious zoonotic disease caused by bacteria belonging to Mycobacterium tuberculosis complex. In sub-Saharan African countries like Chad, TB is endemic and causes a high burden in humans and animals through morbidity, and mortality, and reduced productivity in livestock.To effectively prevent and control the disease, strong coordination between policy makers, health and veterinary services, civil society organizations, and communities is needed. This requires an understanding of the knowledge of communities regarding TB. However, such knowledge is underinvestigated, especially in rural areas. The main objective was to investigate the knowledge, attitudes, and practices (KAP) of Chadian rural communities to better involve them in TB surveillance programs. A survey was conducted in 2021 in five rural health centers. Face-to-face interviews were conducted with suspected TB patients and data on KAP were recorded and analyzed. In total, 139 participants were enrolled. Overall, the knowledge and attitude of the participants was found to be good to moderate, with 126 (90.6%) and 97 (69.7%) had good knowledge and attitudes, respectively. However, their practices were found to be rather weak, with only 40 (28.7%) of participants having good practices. Men were found to have a good knowledge significantly more often when compared to women. Poor attitude was significantly associated with a mobile lifestyle compared to settled, and with farmers (mainly engaged in agriculture) when compared to breeders (livestock keepers). Poor practice was associated with men compared to women, and with settled compared to mobile lifestyle. Good practice was found to be in line with good knowledge and good attitude, however for both analyses the association was not significant (OR knowledge = 5.83 (95% C.I. 0.68-42.83), p = 0.112; OR attitude = 2.09 (95% C.I. 0.87-5.04), p = 0.100). Attitude was not found to be associated with knowledge (OR = 1.03 (95% C.I. 0.30-3.55), p = 0.964). Our study highlights the need for targeted sensitizations and awareness campaigns for the study groups with poor knowledge and attitudes and include practical training to specifically increase the level of good practice, rather than simply providing pure knowledge transfer.